Acute Liver Failure Associated with Levetiracetam and Lacosamide Combination Treatment for Unspecified Epileptic Disorder. (19th August 2013) - Gutiérrez-Grobe, Ylse; Bahena-Gonzalez, Jose Antonio; Herrera-Gomar, Magali; Mendoza-Diaz, Pedro; García-López, Sandra; González-Chon, Octavio
Abstract : Background and Aim . Levetiracetam is a second-generation antiepileptic drug. It is approved as an adjunctive treatment of partial onset seizures with or without secondary generalization. It is considered safe with less than 1% of patients with transient elevations of liver enzymes. Methods . We report a case of acute liver failure secondary to Levetiracetam in combination with Lacosamide documented with a liver biopsy. Results . Liver biopsy demonstrated acute liver injury with a predominant submassive necrosis pattern and features of a drug-induced hepatitis. Conclusions . This is the first published case of acute liver failure due to antiepileptic therapy with Levetiracetam in combination with Lacosamide.